Detection of delamination of steel–polymer sandwich composites using acoustic emission and development of a forming limit diagram considering delamination - Jewook Yang; Sungjin Han; Woong-Ryeol Yu (Heliyon, 2023)
The formability of steel–polymer sandwich composites was investigated using a new forming limit diagram (FLD) while considering delamination and fracture. The acoustic emission (AE) technique was used to observe delamination during the forming process. Several tests, including tensile and lap shear tests, were performed to identify the AE features of delamination. In addition, finite element simulations were carried out using the cohesive zone model to predict the delamination of steel–polymer sandwich composites. An FLD of the sandwich composite was also constructed using the finite element model. Finally, the effect of interfacial adhesion on the formability of sandwich composites was investigated, from which the optimal condition for interfacial adhesion (in terms of ensuring the formability of the sandwich composite) was obtained.